VALIDATION OF DERIVED EQUATION USING ENERGY TECHNIQUE FOR CALCULATING THE CRITICAL BUCKLING LOAD FOR INTERMEDIATE AND LONG COLUMNS - Ahmed Naif Al-Khazaraji; Samir Ali Al-Rabii; Hameed Shamkhi Al-Khazaali (Journal of Engineering and Sustainable Development, 2016)
A new equation  has  been  derived  using  energy  technique  (dummy  load  method)  to describe the buckling behavior of intermediate and long columns under dynamic buckling loads compression load and  under  dynamic  combined  load  with  consider  of  the  initial  imperfections  of  the  columns  and  the effect  of  eccentricity.  The  results  of  this  equation  are  compared  with  the  experimentally  results  of  40 specimens of AISI 303 stainless steel intermediate and long columns tested under dynamic compression loading  (compression  and  torsion)  and  under  dynamic  combined  loading  (compression,  bending,  and torsion) by using a rotating buckling test machine, and it be found that the derived equation may be used to predict of the theoretical critical buckling load Pcr under both dynamic compression and combined load with maximum percentage error is 19.3% and 16.8%, respectively.